PENGARUH PERBANDINGAN MEDIA TANAM TERHADAP PERTUMBUHAN TANAMAN CABAI KERITING (Capsicum annum L) TERHADAP PERTUMBUHAN TANAMAN CABAI KERITING PADA STADIA BIBIT - Widiastuti, Tri; Juhariah, Jujuk; Muryanto, Sigit (Universitas Boyolali, 2023)
This study aims to determine which media is the most optimal and affects the growth of curly chilies at the seedling stage. The experiment used a completely randomized design (CRD with 4 treatment combinations of soil media, manure, husk charcoal and sawdust, repeated 5 times with 10 samples per replication. Data analysis used analysis of variance (Anova) at 5% level and then DMRT test at 5% level.This research was carried out in 4 stages. Phase I: Preparation of premises, tools and materials; Stage II: a) Mixing the planting media according to the provisions, b) Putting the media into polybags according to the code; Stage III: Curly chili seeds; Stage IV: Observation of curly chili seeds.The results of the study were concluded as follows:• Based on the results of research and observations that have been made, it is concluded that code B observations are generally better than other treatments. From the parameters of plant height and stem diameter showed a significant difference.• In the observation of the number of leaves, no significant difference was found starting from observations when the curly chili plants were 10 to 30 DAP.• The effect of the amount of manure on the growth of curly chili plants in the vegetative phase can be seen in the average value of each parameter of the observations made.